EVALUATING THE PERFORMANCE OF ONLINE FOOD DISTRIBUTION SYSTEMS: A CUSTOMER PERSPECTIVE IN JAMBI CITY - Bella Suryani; Achmad Mulyono; Sandi Yudha Barri Zaqy (Journal of Applied Accounting And Business, 2025)
This study aims to analyze the influence of delivery delays, order inaccuracies, and courier capacity limitations on the distribution performance of online food delivery (OFD) services in Jambi City from a customer perspective. This study used a quantitative approach with 100 respondents who had used OFD services more than twice. Data were collected through an online questionnaire and analyzed using multiple linear regression with the help of SPSS. The results showed that all three independent variables simultaneously had a significant effect on distribution performance. Partially, the variables of order inaccuracies and courier capacity limitations had a positive and significant effect on distribution performance, while delivery delays had no significant effect. The Adjusted R Square value of 39.4% indicates that the model is able to explain variations in distribution performance quite well. These findings indicate that the effectiveness of the courier operational system and the accuracy of order processing play an important role in improving the efficiency of the OFD supply chain in medium-sized urban areas such as Jambi. The results of this study are expected to provide a strategic basis for service providers in improving delivery systems and logistics capacity management.